2005
DOI: 10.1111/j.1439-0507.2005.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Erschwerter Verlauf von Ösophagusperforationen durch Pilzinfektion

Abstract: Perforations of the oesophagus are characterized by a high mortality rate, varying between 7 and 49%. In the analyzed group of patients between the years 1986 and 2003, the mortality rate of 28% was caused by septic complications such as mediastinitis and pneumonia. Microbiological examinations of samples from different locations and various secretions, detected mycoses in 28% of the patients (n = 16). Compared with the total of mycoses, a higher mortality of 50% was calculated. The invasive Candida infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In their series of 58 patients,Jungbluth et al found that the mortality rate was 50% among patients with positive fungal cultures compared with 28% overall 22 . The mean time spent in the ICU was greater in the group of patients with positive fungal cultures and this group was also more likely to develop septic complications such as mediastinitis, pneumonia and empyema.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their series of 58 patients,Jungbluth et al found that the mortality rate was 50% among patients with positive fungal cultures compared with 28% overall 22 . The mean time spent in the ICU was greater in the group of patients with positive fungal cultures and this group was also more likely to develop septic complications such as mediastinitis, pneumonia and empyema.…”
Section: Discussionmentioning
confidence: 98%
“…Jungbluth et al recommend only targeted therapy, 22 despite the high risk of complications, while Bauer et al advocate empirical therapy for all cases although their recommendation is only based on a report of two cases 11 …”
Section: Discussionmentioning
confidence: 99%